2021
DOI: 10.48550/arxiv.2103.11293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis and observation of optical skyrmionic structure in free space

Abstract: The skyrmion, which is characterised by a topological integer, is a structure that is topologically stable against local disturbances. The huge potential of skyrmions for use in magnetic storage systems has drawn considerable research interest among physicists. Recently, the optical skyrmion was discovered and has some excellent properties. However, these optical skyrmions have been observed, for example, in surface plasmons that consist of evanescent waves. This type of optical skyrmion is difficult to manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…1). Previous work has relied on using this definition of n to evaluate skyrmion numbers, 12,20,21 however, a property of derivatives is their inherent sensitivity to noise, making experimental evaluation challenging. We have recently derived an alternative definition for the skyrmion number based on polarisation singularities and associated winding numbers and demonstrated that this definition provides a robust and accurate way to determine skyrmion numbers from experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…1). Previous work has relied on using this definition of n to evaluate skyrmion numbers, 12,20,21 however, a property of derivatives is their inherent sensitivity to noise, making experimental evaluation challenging. We have recently derived an alternative definition for the skyrmion number based on polarisation singularities and associated winding numbers and demonstrated that this definition provides a robust and accurate way to determine skyrmion numbers from experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest to the experimentalist are 2D skyrmions, sometimes called 'baby skyrmions', which can be realized in paraxial beams, offering an easily accessible and re-configurable platform for the investigation of topological features and their propagation dynamics. [14][15][16][17][18][19] Unlike magnetic skyrmions, freely propagating paraxial optical skyrmions are only constrained by Maxwell's equations, and therefore offer a versatile platform for the investigation of exotic topological structures. [20] The generation of topological states of light opens up new avenues for the controlled interaction of DOI: 10.1002/lpor.202300155 photons with material quasi-particles such as plasmons, phonons, and excitons.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, in free space, only the spin properties of special optical beams were investigated. However, for an arbitrary structured light which carries the inhomogeneities of intensity, phase, polarization, and singularities, a unified methodology is lacking in describing the dynamical evolving of momentum and angular momentum, especially regarding paraxial focusing, imaging, and scattering systems. Moreover, although optical beams in the free space can form skyrmionic beams, the Gouy phase governs the continuous evolution of polarization structures in the propagating beam, whereas SAM is a good candidate in describing the topological invariants of propagating optical beams. Therefore, understanding the spin–momentum properties of paraxial optical fields is meaningful in providing a guide for spin-state manipulation.…”
Section: Introductionmentioning
confidence: 99%